Peluang dan Tantangan Iman Kristen dalam Bingkai Teologi Agama-Agama - Yakup Hariyanto (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
In Indonesia, the Christian faith is often misunderstood in the context of religious pluralism. Aware of the multi-religious nature of this nation, consideration arises as to what appropriate ideas can be applied to communicating the Christian faith within the context of interfaith theology. The challenges and opportunities in communicating the Christian faith must also be considered. Challenges within interfaith communities include the potential for exclusivism and dogmatism, pluralism, relativism, and inclusivism. These pose significant challenges and dangers to one's faith. If the confession that Jesus is the only Way of Salvation is not sensitive to these circumstances, it can erode, leading to a tendency to deny and equate all religions with the same. This research uses a qualitative method focused on literature review, where sources are obtained from books, journals, and other scholarly works. All scientific references used align with the theme of this paper, namely, "Opportunities and Challenges of Christian Faith Within the Framework of the Theology of Religions."